Encuentros con dueños, duendes y diablos: intersubjetividad, movimiento y paisaje en los caminos de las Quebrada de Humahuaca = Encounters with dueños, goblins and devils : intersubjectivity, movement and landscape along the paths of Quebrada de Humahuaca - Fontes, Cristina (Ciencias sociales y religión, 2020)
From a perspective based on the anthropology of experience, this paper analyzes the relationships of intersubjectivity that the traveler establishes with other non-human beings: dueños, devils and goblins) while traveling through the Andean landscape. Research methodology consisted of taking part of the treks in the community and of those that connects it with neighboring localities. In addition, open interviews were held in order to collect data on their experience when walking certain areas of the landscape, their perception of them and the practices and rituals they perform. As a result of the study, it was observed that the use of certain corporal patterns while walking constitutes an embodied way to express the values and principles that regulate the social organization of the Andean peoples.